Acetate Templating on Digital Images Is More Accurate Than Computer‐based Templating for Total Hip Arthroplasty. Issue 12 (December 2015) - Petretta, Robert; Strelzow, Jason; Ohly, Nicholas E.; Misur, Peter; Masri, Bassam A.
Abstract: Background: Templating is an important aspect of preoperative planning for total hip arthroplasty and can help determine the size and positioning of the prosthesis. Historically, templating has been performed using acetate templates over printed radiographs. As a result of the increasing use of digital imaging, surgeons now either obtain additional printed radiographs solely for templating purposes or use specialized digital templating software, both of which carry additional cost. Questions/purposes: The purposes of this study was to compare acetate templating of digitally calibrated images on an LCD monitor to digital templating in terms of (1) accuracy; (2) reproducibility; and (3) time efficiency. Methods: Acetate onlay templating was performed directly over digital radiographs on an LCD monitor and was compared with digital templating. Five separate observers participated in this study templating on 52 total hip arthroplasties. For the acetate templating, the digital images were magnified to the scaled reference on the templates provided by the manufacturer (ratio 1.2:1) before templating using a 25‐mm marker as a reference. Both the acetate and digital templating results were then compared with the actual implanted components to determine accuracy. Interobserver and intraobserver variability was determined by an intraclass correlation coefficient. Observers recorded time to complete templating from the time of complete upload of patients' imaging onto the system to completion of templating. Results: Both acetate and digital templates demonstrated moderate accuracy in predicting within one size of the eventual implanted acetabular cup (77% [199 of 260]; 70% [181 of 260], respectively; p = 0.050; 95% confidence interval [CI], 0.058‐0.32), whereas acetate templating was better at predicting the femoral stem compared to digital templating (75% [195 of 260]; 60% [155 of 260], respectively; p < 0.001; 95% CI, 0.084‐0.32). Acetate templating showed moderate to substantial interobserver agreement (cup intraclass correlation coefficient [ICC] = 0.55; 95% CI, 0.14‐0.86; femoral ICC = 0.75; 95% CI, 0.39‐0.95) and both methods showed almost perfect intraobserver agreement in reproducibility (acetate cup ICC = 0.82; 95% CI, 0.66‐0.97; acetate femoral ICC = 0.86; 95% CI, 0.74‐0.97; digital cup ICC = 0.82; 95% CI, 0.68‐0.97; digital femoral ICC = 0.88; 95% CI, 0.77‐1.0). Acetate templating could be performed more quickly (acetate mean 119 seconds; range, 37‐220 seconds versus 154 seconds; range, 73‐343 seconds; p < 0.001). Conclusions: Acetate onlay templating on digitally calibrated images can be a reliable substitute for digital templating using specialized software. It is quicker to perform and much less expensive. Hospitals and practices need not purchase expensive software, particularly at lower volume centers. Level of Evidence: Level III, diagnostic study.